2011
DOI: 10.1177/0149206311415280
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Antecedents and Consequences of Leader-Member Exchange

Abstract: Although leader-member exchange (LMX) was identified in the literature nearly 40 years ago, a comprehensive empirical examination of its antecedents and consequences has not been conducted. The authors’ examination included 247 studies, containing 290 samples, and 21 antecedents and 16 consequences of LMX quality. Results indicated that while leader behaviors and perceptions, follower characteristics, interpersonal relationship characteristics, and contextual variables represent significant groups of LMX antec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

62
1,416
5
28

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,281 publications
(1,586 citation statements)
references
References 290 publications
62
1,416
5
28
Order By: Relevance
“…As LMX has a direct effect on work engagement and an indirect effect on WFE, high-quality supervisor-subordinate relationship is the crucial success factor for promoting the positive work-family interactions and cultivating employees' positive feelings about their jobs. Past studies have evidenced that LMX is associated with leaders' behaviors and personality [2]. In developing high-quality LMX, appropriate selection and trainings of managers are especially important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As LMX has a direct effect on work engagement and an indirect effect on WFE, high-quality supervisor-subordinate relationship is the crucial success factor for promoting the positive work-family interactions and cultivating employees' positive feelings about their jobs. Past studies have evidenced that LMX is associated with leaders' behaviors and personality [2]. In developing high-quality LMX, appropriate selection and trainings of managers are especially important.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the quality of this relationship influences followers' work attitudes, behaviors, and performance [1]. In accordance with LMX theory, accumulated research has shown that maintaining a high-quality LMX relationship is beneficial to the organization in terms of favorable employee attitudes and behaviors outcomes, such as organizational commitment, job satisfaction, and job performance [2]. Despite these established findings, less attention has been paid to the potential linkage between LMX and work engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, subordinates' restraint from harming their leaders (e.g., by revealing leaders mistakes or weaknesses) is likely to build trust and high quality leader-member exchange (LMX) because these restraint-based interactions represent interpersonal exchanges in which leaders and followers build a reciprocal cycle of mutual obligation (e.g., Dulebohn, Bommer, Liden, Brouer & Ferris, 2012;Graen & Uhl-Bien, 1995). High quality LMX, in turn, should have a positive effect on perceptions of the subordinate's performance because high quality LMX impacts on performance-related and attitudinal variables (see Dulebohn et al, 2012;and Gerstner & Day, 1997 for reviews).…”
Section: Perspective Taking and Its Consequencesmentioning
confidence: 99%
“…High quality LMX, in turn, should have a positive effect on perceptions of the subordinate's performance because high quality LMX impacts on performance-related and attitudinal variables (see Dulebohn et al, 2012;and Gerstner & Day, 1997 for reviews).…”
Section: Perspective Taking and Its Consequencesmentioning
confidence: 99%
“…One of the main premises of LMX has been the centrality of the supervisor in the development of LMX and the quality of exchange (Erdogan et al, 2006;Walumbwa, Mayer, Wang, Wang, Workman, & Christensen, 2011). However, recent research on LMX has begun to look at the subordinate as an equal counter part to the supervisor in the LMX development process (Dulebohn, Bommer, Liden, Brouer, & Ferris, 2012). Although the supervisor has been viewed as the prominent initiator of the development and quality of LMX, it is conceivable that subordinates with strong organization connections and access to valuable resources within the organization can potentially have the same impact.…”
Section: Leader-member Exchange (Lmx)mentioning
confidence: 99%